PERAN SERTA MASYARAKAT DALAM PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Yasminingrum Yasminingrum (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2018)
Protection and environmental management to ensure the fulfillment and protection of the environment as a part of human rights. As part of the human rights protection and management of the environment in the use of natural resources implemented harmonious, harmonious and balanced with environmental functions. The use of natural resources is based on government policies that are imbued with the obligation to conserve the environment and realize the goal of sustainable environmental development. One way to realize the goal of environmentally sustainable development is to optimize the participation of the community in the protection and management of the environment.